Eccentric strengthening vs. conventional therapy in sub-acute stroke survivors: a randomized controlled trial - Kalthoum Belghith; Kalthoum Belghith; Mustapha Zidi; Lhéo Vincent; Lhéo Vincent; Jean-Michel Fedele; Rayan Bou-Serhal; Wael Maktouf (Frontiers in Neurology)
Spastic paresis, a frequent consequence of stroke, is characterized by both neurological and muscular alterations, leading to decreased muscle strength, increased passive muscle stiffness, and subsequently, diminished functional capacity. Although conventional rehabilitation programs are effective in enhancing muscle strength, they often fail to yield clinically significant improvements in functional capacities. Eccentric Training (ET) has shown promise in addressing the shortened muscle fascicle lengths and joint contractures commonly observed in stroke survivors. Despite the prevalence of contractures and rigidity in this population, the effects of ET on the structural and mechanical properties of muscles remain underexplored. This study aims to investigate the impact of ET on gait speed in sub-acute stroke patients compared to conventional therapy. Additionally, we aim to explore the effects of ET on the mechanical properties, structural characteristics, and neuromuscular parameters of the plantar flexors. A randomized controlled trial will be conducted, adhering to CONSORT guidelines, with participants assigned to either a Conventional Therapy Group or an Eccentric Training Group. Assessments will be conducted at baseline, and after ET intervention, encompassing clinical, biomechanical, and functional evaluations. This study seeks to provide empirical evidence on the efficacy of ET in improving motor outcomes in sub-acute stroke patients, thereby informing more effective rehabilitation strategies.